SNF3 as High Affinity Glucose Sensor and Its Function in Supporting the Viability of Candida glabrata under Glucose-Limited Environment - Ng, Tzu Shan; Chew, Shu Yih; Rangasamy, Premmala; Mohd Desa, Mohd N.; Sandai, Doblin; Chong, Pei Pei; Than, Leslie Thian Lung (Frontiers in Microbiology, 2015)
Candida glabrata is an emerging human fungal pathogen that has efficacious nutrient sensing and responsiveness ability. It can be seen through its ability to thrive in diverse range of nutrient limited-human anatomical sites. Therefore, nutrient sensing particularly glucose sensing is thought to be crucial in contributing to the development and fitness of the pathogen. This study aimed to elucidate the role of SNF3 (Sucrose Non Fermenting 3) as a glucose sensor and its possible role in contributing to the fitness and survivability of C. glabrata in glucose-limited environment. The SNF3 knockout strain was constructed and subjected to different glucose concentrations to evaluate its growth, biofilm formation, amphotericin B susceptibility, ex vivo survivability and effects on the transcriptional profiling of the sugar receptor repressor (SRR) pathway-related genes. The SNF3Δ strain showed a retarded growth in low glucose environments (0.01% and 0.1%) in both fermentation and respiration-preferred conditions but grew well in high glucose concentration environments (1% and 2%). It was also found to be more susceptible to amphotericin B in low glucose environment (0.1%) and macrophage engulfment but showed no difference in the biofilm formation capability. The deletion of SNF3 also resulted in the down-regulation of about half of hexose transporters genes (4 out of 9). Overall, the deletion of SNF3 causes significant reduction in the ability of C. glabrata to sense limited surrounding glucose and consequently disrupts its competency to transport and perform the uptake of this critical nutrient. This study highlighted the role of SNF3 as a high affinity glucose sensor and its role in aiding the survivability of C. glabrata particularly in glucose limited environment.